Commute Time to School and Child Labour: Evidence from China. - Chen, Liping; Chen, Yang; Lin, Jiada; Shen, Zhuyi; Wang, Zhifeng (Journal of Development Studies, 2025)
Child labour presents a pervasive challenge in developing nations, significantly impacting long-term economic growth by hindering the accumulation of human capital. This study utilises data from the China Family Panel Studies to investigate the impact of commute time to school on child labour. The empirical results indicate that a one-hour increase in a child's commute time to school correlates with a statistically significant increase of 6.3 percentage points in the likelihood of the child engaging in the labour market, as well as an increase of 2.3 hours in weekly working hours. Moreover, the mechanism analysis suggests that longer commute time reduces children's learning time, resulting in lower academic performance and educational expectations. Consequently, this increases the likelihood of children joining the labour market during compulsory education. These results underscore the need for enhancing transportation infrastructure and optimising school locations in developing nations to counteract child labour by shortening commute times and improving educational access.